Use and Non-Use of Internet Banking Among Elderly People in Nigeria - Omotayo, Funmilola Olubunmi (International Journal of Social Sciences and Management, 2020)
Existing research in electronic banking has not deeply investigated the determinants of use and non-use of Internet Banking (IB) among the older adults who have been found to exhibit reluctance in using ICT. This study, therefore, investigates the factors that influence use and not use IB among elderly people in the Ibadan metropolis, Nigeria. Survey research design was adopted. Findings indicate that, in addition to the TRA (attitude and subjective norms) and TAM (perceived usefulness and perceived ease of use) variables, trust, self-efficacy, security and facilitating conditions are the factors the elderly population consider in choosing to use or not using IB. Findings also reveal that the non-users have the intention of using IB in the future, while the users have the intention of continuing using IB. This study is novel in the sense that no known study have investigated use and non-use of IB among the elderly in Nigeria in a single study. The paper could assist policymakers in promoting and implementing policies that would ensure the financial inclusion of the elderly and reduce the digital divide between this group and the younger ones. Int. J. Soc. Sc. Manage. Vol. 7, Issue-2: 42-54